Pengaruh Kompetensi Sumber Daya Manusia, Sistem Teknologi Informasi, Sistem Pengendalian Intern Dan Standar Akuntansi Pemerintahan Terhadap Kualitas Laporan Keuangan Pemerintah Daerah (Studi Empiris Organisasi Perangkat Daerah Kabupaten Jepara) - Rachmat Luthfi Sulaiman; Nashirotun Nisa Nurharjanti (LPPM Universitas Putera Batam, 2022)
Financial reports are a medium for an entity, in this case the local government to account for its financial performance to the public. Local governments must be able to present financial reports that contain quality financial information. This study aims to determine the effect of Human Resource Competence, Information Technology Systems, Internal Control Systems and Government Accounting Standards on the Quality of Local Government Financial Reports. While the population in this study were employees of Regional Apparatus Organizations (OPD) in Jepara District. The sample in this study were finance and accounting staff at OPD Jepara District. The research object used was 35 OPD, from 100 respondents who were finance and accounting staff at the Regional Apparatus Organization (OPD) of Jepara District. The results of this study prove that the competence of human resources and government accounting systems have no effect on the quality of financial reports. Meanwhile, information technology systems and internal control systems affect the quality of financial reports.